Penerapan Model Pembelajaran SQ3R (Survey, Question, Read, Recite, Review) Untuk Meningkatkan Aktivitas dan Hasil Belajar Biologi Siswa Kelas XI IPA-7 di SMA Negeri 2 Kota Ternate - Yeyen Pratiwi Muhtar; Ilham Madjid; Dharmawaty M. Taher (Peneliti.net, 2020)
Education is important in order to improve the quality Human Resources both in terms of spirituality, intelligence, and skills to support his life. This study aims to determine the application of the Survey, question read, recite, review (SQ3R) learning model to the activities of class XI IPA-7 students at SMA Negeri 2 Ternate City and to determine the application of the SQ3R learning model to the biology learning outcomes of class XI IPA- 7 students. at SMA Negeri 2 Ternate City. This type of research is Classroom Action Research (CAR) or what is called Classroom Action Research (CAR), which is a scientific activity carried out by designing, implementing, observing, and reflecting on actions through several cycles collaboratively. The results showed that the application of the SQ3R learning model could increase the activity of class XI IPA-7 at SMA Negeri 2 Ternate City on the material of the Respiratory System. The results of observations of teacher activities in the first cycle were 68.23%, the second cycle increased to 83.5%. In the results of the observation of student activity in the first cycle, namely 61.17%, the second cycle increased to 76.47%, and the results of learning biology material for the respiratory system with the application of the SQ3R learning model in class XI IPA-7 students of SMA Negeri 2 Ternate City have increased from cycle I and cycle II. Cycle I there were 23 students with a percentage of 76.66% who entered the incomplete category and 7 students with a percentage of 23.34% in the complete category. In the second cycle, the students' completeness scores increased to 80%. This proves that the learning outcomes of respiratory system biology material with the application of the Survey, question read, recite, review (SQ3R) learning model have increased.